Urgensi Filsafat Pendidikan dalam Menyikapi Krisis Moral Peserta Didik di Era Digital - Rokiba Hasibuan; Leli Hasanah Lubis (Jurnal Zeniusi, 2025)
The moral crisis of students in the digital era is a serious challenge in the world of modern education. The rapid advancement of information and communication technology has had a major impact on the way of thinking, behaving, and forming the values ​​of the younger generation. Open information without filters, instant culture, and the influence of social media have led to a decrease in empathy, a weakening of respect, and a strengthening of moral relativism. This study aims to examine the urgency of educational philosophy as a reflective approach in responding to the moral crisis of students. This study uses a qualitative approach through a library research method by reviewing educational philosophy literature, ethical theories, and research results related to character education and the digital era. The results of the study show that educational philosophy plays an important role in forming an ethical framework of thinking, strengthening the foundation of values, and instilling critical moral awareness in students. In addition, educational philosophy also provides a new direction for teachers and educational institutions to integrate noble values ​​into the learning process. Thus, educational philosophy becomes a strategic foundation in building a generation that is not only intellectually intelligent but also morally mature.